Stimulation of the epithelial sodium channel (ENaC) by the serum- and glucocorticoid-inducible kinase (Sgk) involves the PY-motifs of the channel but is independent of sodium feedback inhibition - Rauh, Robert; Dinudom, Anuwat; Fotia, Andrew B.; Paulides, Marios; Kumar, Sharad; Korbmacher, Christoph; Cook, David. I. (Pflügers Archiv: European Journal of Physiology, 2006)
The epithelial sodium channel (ENaC) is the major mediator of sodium transport across the apical membranes of the distal nephron, the distal colon, the respiratory tract and the ducts of exocrine glands. It is subject to feedback inhibition by increased intracellular Na+, a regulatory system wherein the ubiquitin protein ligases, Nedd4 and Nedd4-2, bind to conserved PY motifs in the C-termini of ENaC and inactivate the channel. It has been proposed recently that the kinase Sgk activates the channel as a consequence of phosphorylating Nedd4-2, thus preventing it from inhibiting the channels. This proposal predicts that Sgk should interfere with Na+ feedback regulation of ENaC. We have tested this prediction in Xenopus laevis oocytes and in mouse salivary duct cells and found that in neither system did increased activity of Sgk interrupt Na+ feedback inhibition of ENaC. We found, however, that Sgk stimulation was largely abolished in oocytes expressing ENaC channels with C-terminal truncations or mutated PY motifs. We were also unable to confirm that Sgk directly interacts with Nedd4-2 in vitro. We conclude that the stimulatory effect of Sgk on ENaC requires the presence of the channel's PY motifs, but it is not due to the interruption of Na+ feedback regulation. © Springer-Verlag 2006.
UnivIS-Import:2015-03-09:Pub.2006.med.IPK.LPVP.stimul_9
Keywords: Amiloride; EnaC; Nedd4; Sgk; Ubiquitin protein ligases